2022
DOI: 10.1021/acsaelm.2c00587
|View full text |Cite
|
Sign up to set email alerts
|

High-Responsivity Vis–NIR Photodetector Based on a Ag2S/CsPbBr3 Heterojunction

Abstract: Quantum dots (QDs) have gained significant interest in optoelectronic devices due to their excellent properties. Single-QD materials limit the high performance of photodetectors (PDs). The performance of PDs is enhanced by combining two dissimilar materials to form a heterostructure. The high responsivity vis−NIR photodetector based on a Ag 2 S/CsPbBr 3 heterojunction is presented in this work. Using CsPbBr 3 QDs as the first absorption layer and Ag 2 S QDs as the second absorption layer, a bipolar carrier tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The CsPbBr 3 photosensors showed maximum photocurrent and critical parameter values at a specific wavelength in the range of 400–800 nm (541 nm for CsPbBr 3 /MoS 2 photosensor and 535 nm for CsPbBr 3 /MoS 2 with parylene-C photosensor). The maximum value of responsivity increased from 3.7 A/W to 6.1 A/W, the detectivity increased from 1.6 × 10 13 Jones to 3.4 × 10 13 Jones, and the EQE increased from 705.9% to 1392.1% after parylene-C coating under bias potential of 0.5 V. The analytical parameters from this and previous studies are summarized in Table . Additionally, the responsivity and detectivity of the photosensor in this study were significantly higher than those of previously reported perovskite photosensors, as shown in Figure S6b.…”
Section: Results and Discussionmentioning
confidence: 46%
“…The CsPbBr 3 photosensors showed maximum photocurrent and critical parameter values at a specific wavelength in the range of 400–800 nm (541 nm for CsPbBr 3 /MoS 2 photosensor and 535 nm for CsPbBr 3 /MoS 2 with parylene-C photosensor). The maximum value of responsivity increased from 3.7 A/W to 6.1 A/W, the detectivity increased from 1.6 × 10 13 Jones to 3.4 × 10 13 Jones, and the EQE increased from 705.9% to 1392.1% after parylene-C coating under bias potential of 0.5 V. The analytical parameters from this and previous studies are summarized in Table . Additionally, the responsivity and detectivity of the photosensor in this study were significantly higher than those of previously reported perovskite photosensors, as shown in Figure S6b.…”
Section: Results and Discussionmentioning
confidence: 46%
“…As shown in Figure 1b, the conduction band minimum (CBM) and valence band maximum (VBM) of CsPbBr 3 NCs are located at −3.6 eV and −5.9 eV, respectively. 27 The lowest unoccupied molecular orbital (LUMO) and highest occupied molecular orbital (HOMO) of Y6 are at −4.1 eV and −5.6 eV. 21 When the two semiconductors make contact, a built-in electric field is created due to the difference in Fermi levels, thus forming a heterojunction, as shown in Figure 1c.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In eqn (1), Y, Y 1 , and Y 2 are amplitudes, t represents time, the short-lived decay component (t 1 ) corresponds to trapassisted recombination, and the long-lived decay component (t 2 ) corresponds to carrier recombination. 38,45,46 The average lifetime (t ave ) was computed using eqn (2). Decay-fitting parameters (Y 1 , Y 2 , t 1 , and t 2 ) and calculated average lifetimes (t ave ) of the decay curves are listed in Table S4 (ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…Lead-halide perovskite nanocrystals (LHPNC) have been considered next-generation light-emitting semiconductors with promising applications in optoelectronics, such as photovoltaic cells, 1 photodetectors, 2 low-threshold lasers, 3 light-emitting diodes (LEDs) for solid-state lighting and display technologies, 4 anticounterfeiting, 5 sensors 6 and X-ray scintillators 7 because of their narrow PL, tunable bandgap, near unity photoluminescence quantum yield (PLQY), reduced fluorescent blinking, high defect tolerance, and efficient radiative recombination, which is achieved through the confinement of excitons in small sizes. 8 Significant advances have been made in the synthesis of LHPNCs using various techniques, which have enabled precise control of their composition, size, and shape to produce emission that spans the entire spectrum, from near-ultraviolet (UV) to near-infrared.…”
Section: Introductionmentioning
confidence: 99%